Reação de germoplasmas de melão a Fusarium solani f. sp. cucurbitae e herança da resistência do acesso AC-33 a Monosporascus cannonballus - Guimarães, Izabel Macedo (Universidade Federal Rural do Semi-Árido, 2016)
The melon cultivation in semi-arid northeast in consecutive cycles has generated problems caused by fungi inhabitants of the soil, such as Fusarium solani and M. cannonballus. The use of resistant cultivars is an interesting measure for the management of the disease. For this reason, it is important identify sources of resistance and study their inheritance. The objectives of this work were: a) to evaluate the reaction of melon accessions to F. solani f. sp. Cucurbitae; b) to evaluate the reaction of accessions and study the inheritance of resistance of accession AC-33 to M. cannonballus. In the first experiment, we evaluated twenty-one accessions in a completely randomized design in greenhouse. Two isolates were inoculated fifteen days after sowing by the toothpick. The assessment was done Thirty days after inoculation with a scale scored from zero to four. The accessions AC-01, AC-09, AC-42, AC-45, AC-50 and the cultivar 'Doublon' are the most promising materials for use in breeding programs for resistance to F. solani or as rootstocks. In the second experiment, sixteen accessions and line OF-02 were evaluated in a completely randomized design. We used the isolated MC-16 to infestation of a mixture (1:1:1) with soil, peat, and sand previously sterilized with the addition of a concentration of 20 u.f.c./g soil. The evaluation was performed at 45 days using a rating scale (1-5). In the third experiment, we investigated the inheritance of resistance of accession AC-33 crossed with line OF-02 (susceptible). We observed variability in the germplasm investigated for reaction to the fungus. The AC-33 is highly resistant to access M. cannonballus and its resistance is controlled by a major gene with additive and dominant effects and polygenes with additive effects
Keywords: Cucumis melo; Controle genético; Germoplasma; Monogênico; Poligenes; Cucumis melo; Soil-borne pathogens; Genetic control; Germplasm; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA